Nanofiber film with insulin slow-release and barrier functions and preparation method thereof

The Ins-PCL/SF/nHA-M nanofiber film prepared by coaxial electrospinning technology solves the problem that the GBR barrier membrane lacks drug load sustained release function in the repair of diabetic bone defects, realizes the sustained release and barrier function of insulin, and promotes diabetic bone regeneration.

CN119656375APending Publication Date: 2025-03-21GUILIN MEDICAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411835208.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing GBR barrier membrane mainly plays a barrier role in the repair of diabetic bone defects, but does not have the function of drug load sustained release, which cannot solve the problems caused by diabetic bone increase.

Method used

Coaxial electrospinning technology was used to prepare nanofiber films with sustained release insulin and barrier functions. Polycaproliferative PCL, silk fibroin SF and nanohydroxyapatite nHA were used as raw materials, and insulin glargine was used as nuclear layer solution. Ins-PCL/SF/nHA-M nanofiber films were obtained by magnetic stirring and vacuum drying.

Benefits of technology

It realizes that the GBR barrier membrane has the function of sustained insulin load and the function of barrier, and has good mechanical properties and hydrophilicity, which can effectively promote diabetic bone regeneration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656375A_ABST
    Figure CN119656375A_ABST
Patent Text Reader

Abstract

The invention discloses a nanofiber film with insulin slow release and barrier functions, which is characterized in that polycaprolactone (PCL), silk fibroin (SF) and nano-hydroxyapatite (nHA) are used as raw materials, hexafluoroisopropanol (HFIP) is used as a solvent to prepare a shell layer electrostatic spinning solution, insulin glargine (Ins) is used as a core layer electrostatic spinning solution, and coaxial electrostatic spinning is carried out to prepare the nanofiber film with the thickness of 0.1-0.6 mm and the barrier function. An Ins-PCL / SF / nHA-M with hydrophilicity and biocompatibility, and an Ins-PCL / SF / nHA The thin film is composed of nanofibers with the diameter of 300-600 nm, randomly arranged nanofibers with the interval of 1-20 m. The tensile strength is 3.5 to 6 MPa. The preparation method comprises the following steps: placing PCL, SF and nHA in HFIP, carrying out magnetic stirring to obtain a shell layer electrostatic spinning solution, taking Ins as a core layer electrostatic spinning solution, and carrying out coaxial electrostatic spinning and drying. When applied to the field of bone regeneration, the material has a slow release function and a barrier function; the sustained-release function has four release stages, the release days are 39 days, and fibroblasts can be shielded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano-biomedical material engineering, and specifically relates to a nano-fiber film with insulin-slow-release and barrier functions and a preparation method thereof. Background Art

[0002] Alveolar bone defect is one of the difficulties in dental implant treatment for edentulous patients. Periodontal disease, trauma, caries, tumor resection, genetics, and systemic diseases are all causes of alveolar bone defect. At present, the commonly used bone augmentation technology in oral implant clinics is guided bone regeneration (GBR). According to the existing literature 1 (Kofina V, Monfaredzadeh M, Rawal SY, et al. Patient-reported outcomes following guided bone regeneration: Correlation with clinical parameters [J]. Journal of dentistry, 2023: 136.), guided bone regeneration refers to the implantation of bone filling materials in the bone defect area, covering the surface of the bone filling materials with a biological barrier membrane, and thereby blocking the growth of faster-proliferating epithelial cells and fibroblasts, thereby creating an advantageous environment for bone tissue growth, ensuring that osteoblasts with a slower proliferation rate on the bone surface can better enter the bone defect area, while protecting blood clots and promoting the growth of blood vessels to achieve bone regeneration in the bone defect area. Diabetes mellitus (DM) patients will have insulin resistance, which leads to insufficient insulin secretion, resulting in a long-term high-sugar microenvironment in the body, severe inflammatory response, microvascular disease, and high blood sugar that disrupts the balance of osteoblasts and osteoclasts. This problem directly leads to the speed of new bone formation and the quality of new alveolar bone being significantly lower than that of patients without DM.

[0003] At present, the commonly used method for repairing diabetic bone defects is guided bone regeneration. Y, Tatl1U, et al. A clinical prospective study on alveolar bone augmentation and dental implant success in patients with type 2 diabetes [J]. Clin Oral Implants Res, 2015, 26 (11): 1267-1275.) Although guided bone regeneration is used..., GBR barrier membranes mainly play a barrier role in the repair of diabetic bone defects and do not have a sustained-release effect of drug loading. Therefore, GBR barrier membranes cannot solve the problems caused by bone augmentation in diabetes.

[0004] In view of the problem of bone regeneration in diabetic bone defects, the effect of promoting osteogenesis can be achieved by injecting insulin into the bone defect area. However, since the half-life of free insulin is only 20-30 minutes, this type of insulin injection method is not suitable for use in the field of promoting osteogenesis in DM patients. In order to solve the problem of the half-life of free insulin mentioned above, the current common technical means is to achieve a sustained release effect by encapsulating insulin and improve the utilization efficiency of insulin in DM patients. For example, existing document 3 (Xing Wang, Lu Wang, Feng Qi, et al. The effect of a single injection of uniform-sized insulin-loaded PLGA microspheres on peri-implant bone formation [J]. RSC Advances, 2018, 8 (70): 40417-40425. DOI: 10.1039 / C8RA08505F.) adopts the Shirasu porous glass SPG premixed membrane method, which is achieved through the following 5 steps:

[0005] Step 1, mixing an insulin solution and dichloromethane containing PLGA to form a primary emulsion;

[0006] Step 2, mixing the primary emulsion with an external aqueous phase containing PVA and NaCl to form a crude solution;

[0007] Step 3, the crude liquid is squeezed through the SPG membrane to obtain droplets of uniform size;

[0008] Step 4, stirring the emulsion droplets at room temperature for 12 hours, and allowing the solvent to evaporate;

[0009] Step 5, collecting by centrifugation at 1000 g to obtain microspheres.

[0010] This technical solution achieves the sustained release function of insulin by loading insulin into microspheres, with the continuous release time being 60 days.

[0011] However, this technical solution has three technical problems:

[0012] 1. The microspheres are spherical particles with poor plasticity and mechanical strength that cannot meet application requirements, and cannot be used as barrier membranes;

[0013] 1. The preparation process of microspheres is complicated;

[0014] 2. The obtained microspheres will slowly break down under in vitro storage conditions, resulting in higher storage costs.

[0015] In order to solve the above technical problems, the inventor's research group conducted preliminary work, and the existing document 4 (Liang Lihua et al. A three-dimensional insulin-loaded scaffold with sustained release and support functions and its preparation method and application: 202410825005[P][2024-11-24].) used PCL, PLGA, and nHA as shell solutions, and glargine insulin as core solution, and prepared Ins-PCL / PLGA / nHA-M fiber membrane by coaxial electrospinning technology, and then prepared Ins-PCL / PLGA / nHA-3D three-dimensional scaffold by foaming technology to obtain a three-dimensional insulin-loaded scaffold with sustained release and support functions. Although this technical solution enables the insulin-loaded three-dimensional scaffold to obtain drug-loaded sustained release function and support function, as well as good hydrophilic properties, the Ins-PCL / PLGA / nHA-3D obtained by this technical solution also does not have barrier properties. Summary of the invention

[0016] The invention aims at providing a nanofiber film with sustained insulin release and barrier function and a preparation method thereof.

[0017] In order to achieve GBR in patients with diabetic alveolar bone defects, the GBR membrane has both insulin loading and sustained release functions and barrier functions as well as good mechanical functions, the present invention adopts coaxial electrospinning technology to prepare a nanofiber film with insulin sustained release and barrier functions. When performing GBR, it is not necessary for all bone filling materials to be used as insulin carriers. It is only necessary for the barrier membrane to have insulin loading and sustained release functions to achieve the purpose of promoting diabetic bone regeneration.

[0018] To achieve the above object, the present invention is implemented through the following technical solutions:

[0019] A nanofiber film with sustained insulin release and barrier function, using polycaprolactone PCL, silk fibroin SF and nano-hydroxyapatite nHA as raw materials, using hexafluoroisopropanol HFIP as solvent to prepare a shell electrospinning solution, using insulin glargine Ins as a core electrospinning solution, and preparing a nanofiber film Ins-PCL / SF / nHA-M with a coaxial shell-core structure through coaxial electrospinning; the Ins-PCL / SF / nHA-M has hydrophilicity and biocompatibility;

[0020] The Ins-PCL / SF / nHA-M has a thin film structure with a thickness of 0.1-0.6 mm; the Ins-PCL / SF / nHA-M is composed of nanofibers with a diameter of 300-600 nm, the nanofibers are randomly arranged, and the spacing between the nanofibers is 1-20 μm;

[0021] The internal microstructure of the Ins-PCL / SF / nHA-M nanofiber is a coaxial shell-core structure, that is, PCL / SF / nHA encapsulates insulin glargine, wherein PCL / SF / nHA is a shell structure and insulin glargine is a core structure;

[0022] The tensile strength of the Ins-PCL / SF / nHA-M is 3.5-6 MPa.

[0023] A method for preparing a nanofiber film with sustained insulin release and barrier function, comprising the following steps: first, polycaprolactone PCL, silk fibroin SF, nanohydroxyapatite nHA, hexafluoroisopropanol HFIP and insulin glargine Ins meet a certain mass ratio, PCL, SF and nHA are placed in HFIP, and magnetic stirring is performed under certain conditions to obtain a shell electrospinning solution, then, insulin glargine Ins is used as a core electrospinning solution, and coaxial electrospinning is performed with the shell electrospinning solution, and after the electrospinning is completed, the obtained product is vacuum dried to obtain a nanofiber film with sustained insulin release and barrier function, referred to as Ins-PCL / SF / nHA-M;

[0024] The mass ratio of PCL, SF, nHA, HFIP and Ins is 13.3:5.7:1:100:3.18;

[0025] The magnetic stirring condition is that the magnetic stirring time is 12-24h; the vacuum drying condition is that the drying temperature is 25-30°C and the drying time is 12-72h;

[0026] The conditions for the coaxial electrospinning are as follows: before the coaxial electrospinning, the shell electrospinning solution is magnetically stirred for a magnetic stirring time of 12-24 hours, the spinning voltage is 13-15KV, the shell solution injection rate is 0.042-0.06mm / min, the core solution injection rate is 0.015-0.02mm / min, and the collection distance is 10-15cm.

[0027] A nanofiber film with sustained insulin release and barrier function, which has sustained release function and barrier function when used in the field of bone regeneration;

[0028] The sustained-release function is that there are 4 release stages and the release days are 39 days;

[0029] The sustained-release function has four release stages, namely,

[0030] Phase 1 was day 1, with insulin release concentrations ranging from 74.40 to 86.52 pg / mL;

[0031] Phase 2 is from day 2 to day 7, with insulin release concentrations ranging from 98.46 to 240.79 pg / mL;

[0032] The third stage is from day 14 to day 28, and the insulin release concentration ranges from 60.29 to 88.75 pg / mL;

[0033] Phase 4 is from day 28 to day 39, and the insulin release concentration range is 35.15-47.01 pg / mL.

[0034] The technical effects of the present invention have been tested experimentally, and the specific contents are as follows:

[0035] XRD test shows that Ins-PCL / SF / nHA-M contains the characteristic peaks of PCL, SF and nHA at the same time, that is, Ins-PCL / SF / nHA-M is a simple physical composite of PCL, SF and nHA.

[0036] FTIR testing has proved that Ins-PCL / SF / nHA-M simultaneously contains the absorption peaks of the characteristic element chemical bonds of PCL, SF, and nHA, that is, Ins-PCL / SF / nHA-M does not produce new chemical bonds and does not produce chemical reactions.

[0037] Macroscopic morphology tests have shown that Ins-PCL / SF / nHA-M has a thin film structure with a thickness of 0.2 mm.

[0038] SEM tests have shown that Ins-PCL / SF / nHA-M is composed of nanofibers with a diameter of 300-600nm. The nanofibers are randomly arranged with a spacing of 1-20μm.

[0039] TEM tests have proved that the internal microstructure of Ins-PCL / SF / nHA-M nanofibers is PCL / SF / nHA encapsulating glargine insulin, that is, it has a coaxial core-shell structure, and Ins-PCL / SF / nHA-M is an effective carrier for slow and sustained release of drugs.

[0040] The tensile strength test showed that the average tensile strength of Ins-PCL / SF / nHA-M was 4.8 MPa, proving that Ins-PCL / SF / nHA-M has good mechanical properties.

[0041] The contact angle test showed that the contact angle of Ins-PCL / SF / nHA-M was 77.118°, proving that Ins-PCL / SF / nHA-M has good hydrophilicity.

[0042] The live and dead cell staining test proved that there were almost no dead cells in Ins-PCL / SF / nHA-M, which proved that Ins-PCL / SF / nHA-M was non-toxic and biocompatible.

[0043] Insulin release experiments have proved that Ins-PCL / SF / nHA-M has four release stages. The first stage is the first day, and the insulin release concentration range is 74.40-86.52pg / mL; the second stage is the 2nd to 7th day, and the insulin release concentration range is 98.46-240.79pg / mL; the third stage is the 14th to 28th day, and the insulin release concentration range is 60.29-88.75pg / mL; the fourth stage is the 28th to 39th day, and the insulin release concentration range is 35.15-47.01pg / mL; this proves that Ins-PCL / SF / nHA-M has the performance of sustained insulin release.

[0044] The human gingival cell barrier experiment proved that the infiltration depth of human gingival fibroblasts on 0.2 mm Ins-PCL / SF / nHA-M was 20 μm, which proved that human gingival fibroblasts did not penetrate Ins-PCL / SF / nHA-M. In other words, Ins-PCL / SF / nHA-M can prevent human gingival fibroblasts from growing into the defect area, that is, Ins-PCL / SF / nHA-M has a barrier function.

[0045] Therefore, the present invention has the following advantages over the prior art:

[0046] 1. The Ins-PCL / SF / nHA-M obtained by the present invention has both the function of insulin loading and sustained release and barrier human gingival fibroblasts, that is, it can improve the local hyperglycemic microenvironment of DM patients while maintaining the bone formation space;

[0047] 2. Since the present invention selects PCL, SF, nHA and insulin glargine commonly used in the treatment of diabetes as raw materials, a 0.2 mm Ins-PCL / SF / nHA-M film is prepared by coaxial electrospinning technology, so that the GBR barrier membrane not only has barrier properties and insulin load sustained release function, but also has good mechanical properties;

[0048] 3. The preparation process of the present invention is simple, no foaming process is required, and the use of raw materials is reduced;

[0049] 4. The present invention achieves good hydrophilic properties while achieving barrier function. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 is the XRD pattern of Ins-PCL / SF / nHA-M;

[0051] Figure 2 is the FTIR graph of Ins-PCL / SF / nHA-M;

[0052] Figure 3 is the macroscopic morphology of Ins-PCL / SF / nHA-M;

[0053] Figure 4 is the SEM image of Ins-PCL / SF / nHA-M;

[0054] Figure 5 TEM plan view of Ins-PCL / SF / nHA-M

[0055] Figure 6 is the tensile strength bar graph of Ins-PCL / SF / nHA-M;

[0056] Figure 7 is the water contact angle graph of Ins-PCL / SF / nHA-M;

[0057] Figure 8 is the live-dead cell staining image of Ins-PCL / SF / nHA-M;

[0058] Fig. 9 is the cumulative release curve of insulin glargine of Ins-PCL / SF / nHA-M;

[0059] Fig.10 is the staining image of human gingival fibroblasts of Ins-PCL / SF / nHA-M;

[0060] Fig.11 is the depth map of human gingival fibroblast infiltration of Ins-PCL / SF / nHA-M;

[0061] Fig.12 is the water contact angle diagram of Comparative Example 1;

[0062] Fig.13 It is the tensile strength bar graph of Comparative Example 2.

[0063] Fig.14 is the water contact angle diagram of Comparative Example 2; DETAILED DESCRIPTION

[0064] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0065] Example 1

[0066] A nanofiber film with sustained insulin release and barrier function, the specific steps are: first, polycaprolactone PCL, silk fibroin SF, nano hydroxyapatite nHA, hexafluoroisopropanol HFIP and insulin glargine Ins meet a certain mass ratio, PCL, SF, nHA are placed in HFIP, and magnetic stirring is performed under certain conditions to obtain a shell electrospinning solution, then, insulin glargine Ins is used as a core electrospinning solution, and coaxial electrospinning is performed with the shell electrospinning solution, and after the electrospinning is completed, the obtained product is vacuum dried to obtain a nanofiber film with sustained insulin release and barrier function, which is abbreviated as Ins-PCL / SF / nHA-M.

[0067] The mass ratio of PCL, SF, nHA, HFIP and Ins is 13.3:5.7:1:100:3.18;

[0068] The magnetic stirring condition is that the magnetic stirring time is 24 hours; the vacuum drying condition is that the drying temperature is 25° C. and the drying time is 48 hours;

[0069] The coaxial electrospinning conditions are as follows: before the coaxial electrospinning, the shell electrospinning solution is magnetically stirred for 24 hours, the spinning voltage is 13KV, the shell solution injection rate is 0.042mm / min, the core solution injection rate is 0.015mm / min, and the collection distance is 15cm.

[0070] In order to prove the composition of Ins-PCL / SF / nHA-M, XRD test was carried out. At the same time, XRD test was carried out on raw materials PCL, SF and nHA as reference. The test results are shown in Figure 1 As shown in Figure 2, Ins-PCL / SF / nHA-M contains the characteristic peaks of PCL, SF, and nHA. The test results show that the components in Ins-PCL / SF / nHA-M are physically composited, that is, the addition of SF and nHA does not destroy the crystal structure of PCL.

[0071] In order to prove the chemical composition of Ins-PCL / SF / nHA-M, FTIR test was carried out. At the same time, FTIR test was carried out on raw materials PCL, SF and nHA as reference. The test results are shown in Figure 2. Figure 2 As shown in Figure 2, Ins-PCL / SF / nHA-M contains characteristic peaks of PCL, SF and nHA at the same time. The test results show that the components in Ins-PCL / SF / nHA-M are physically composited, that is, no new chemical bonds are generated between SF, PCL and nHA, and no chemical reaction occurs.

[0072] In order to prove the macroscopic morphology of Ins-PCL / SF / nHA-M, macroscopic morphology test was carried out. The test results are shown in Figure 3 As shown, Ins-PCL / SF / nHA-M has a thin film structure with a thickness of 0.2 mm.

[0073] In order to verify the microstructure of Ins-PCL / SF / nHA-M, SEM was performed and the test results are shown in Figure 4 It was shown that Ins-PCL / SF / nHA-M was composed of nanofibers with a diameter of 300-600 nm. The nanofibers were randomly arranged with a spacing of 1-20 μm.

[0074] In order to further prove the internal microstructure of Ins-PCL / SF / nHA-M nanofibers, i.e., the coaxial structure, TEM test was performed. The test results are shown in Figure 5 As shown in the figure, the internal microstructure of Ins-PCL / SF / nHA-M nanofibers is that PCL / SF / nHA encapsulates insulin glargine, that is, it has a coaxial shell-core structure, in which PCL / SF / nHA is a shell structure and Ins is a core structure. The test results show that Ins-PCL / SF / nHA-M is an effective carrier for slow and sustained release of drugs.

[0075] In order to prove the mechanical properties of Ins-PCL / SF / nHA-M, tensile strength test was carried out. Figure 6 As shown in Figure 2, the tensile strength of Ins-PCL / SF / nHA-M is 4.8 MPa. The test results show that Ins-PCL / SF / nHA-M has good tensile strength.

[0076] Further analysis of the mechanical properties shows that according to reference 1 (Raz P, Brosh T, Ronen G, et al. Tensile Properties of Three Selected Collagen Membranes [J]. BioMed research international, 2019, 2019: 5163603), the average tensile strength of the Bio-Gide barrier membrane currently used in clinical practice is 4.6 ± 0.94 MPa. The tensile strength of the Ins-PCL / SF / nHA-M of the present invention exceeds the tensile strength of the current conventional barrier membrane, meets the application requirements, and has good mechanical functions.

[0077] Note: It should be noted that the Bio-Gide barrier membrane in reference 1 does not have the function of sustained release of drug loading.

[0078] At the same time, according to reference 2 (Wang Y, Liu L, Zhu Y, et al. Tri-Layer Core-Shell Fibers from Coaxial Electrospinning for a Modified Release of Metronidazole [J]. Pharmaceutics, 2023, 15 (11).), it can be seen that this technical solution uses polyvinyl alcohol PVA, polycaprolactone PCL, Eudragit RL100 and Eudragit S100 as shell layer solutions, metronidazole as core layer solution, and a drug-loaded fiber membrane obtained by coaxial electrospinning technology. The tensile strength of the drug-loaded fiber membrane is less than 1 MPa. Combined with reference 1, it can be seen that the tensile strength of the drug-loaded fiber membrane obtained in reference 2 is far from meeting the application requirements.

[0079] It can be seen from references 1 and 2 that the Ins-PCL / SF / nHA-M obtained in the present invention has both drug loading sustained-release function and good mechanical function.

[0080] In order to prove the hydrophilicity of Ins-PCL / SF / nHA-M, contact angle test was performed. The test results are shown in Figure 7 As shown, the water contact angle of Ins-PCL / SF / nHA-M is 77.118°. The test results show that Ins-PCL / SF / nHA-M has good hydrophilicity. According to common knowledge in the field, good hydrophilicity can enhance the adhesion to human gingival fibroblasts and promote the activity of osteoblasts, which is beneficial to promote the repair and regeneration of diabetic bone tissue and soft tissue healing.

[0081] In order to prove the biocompatibility of Ins-PCL / SF / nHA-M, live and dead cell staining was performed. The specific test method of live and dead cell staining test is as follows: first, mouse preosteoblasts MC3T3-E1 were inoculated on Ins-PCL / SF / nHA-M and cultured for 3 days. After the culture was completed, the culture medium was aspirated, and then the live and dead cell stain Calcein-AM / PI was added. The cells were incubated for 30 minutes under light-proof conditions. After the incubation was completed, the staining results were tested under a fluorescence microscope, where green cells represent live cells and red cells represent dead cells. The test results are as follows: Figure 8 As shown, the ratio of live cells to dead cells is 99.9:0.1. The test results show that Ins-PCL / SF / nHA-M is non-toxic, that is, it has biocompatibility.

[0082] In order to prove that Ins-PCL / SF / nHA-M has sustained release function, insulin release experiment was conducted. The test results are as follows Fig. 9 As shown, Ins-PCL / SF / nHA-M has four release stages, namely,

[0083] Phase 1 was day 1, with an insulin release concentration of 80.46 pg / mL;

[0084] Phase 2 is from day 2 to day 7, with an insulin release concentration of 169.62 pg / mL;

[0085] The third stage is from day 14 to day 28, when the insulin release concentration is 74.52 pg / mL;

[0086] The fourth stage is from day 29 to day 39, and the insulin release concentration is 41.08 pg / mL.

[0087] The test results showed that the continuous release days of Ins-PCL / SF / nHA-M was 39 days.

[0088] In order to prove that Ins-PCL / SF / nHA-M has barrier properties, a barrier performance test was conducted. The specific test method for the barrier performance test is as follows: first, human gingival fibroblasts HGF were inoculated on Ins-PCL / SF / nHA-M and cultured for 7 days. After the culture was completed, the culture medium was aspirated, and then the cells were fixed with 4% tissue fixative. After that, rhodamine-labeled phalloidin Phalloidin-TRITC was added and incubated for 30 minutes under light-proof conditions. After incubation, the morphology of HGF was tested under a confocal microscope, where blue represents the nucleus and red represents the cytoplasm. The test results are as follows: Fig.10As shown, human gingival fibroblasts can be detected on Ins-PCL / SF / nHA-M. The test results show that Ins-PCL / SF / nHA-M is non-toxic, that is, it is biocompatible.

[0089] The infiltration depth of human gingival fibroblasts was further tested, and the test results were as follows Fig.11 As shown, the infiltration depth of human gingival fibroblasts on 0.2mm Ins-PCL / SF / nHA-M is 20μm. The test results show that human gingival fibroblasts do not penetrate Ins-PCL / SF / nHA-M, and Ins-PCL / SF / nHA-M can prevent human gingival fibroblasts from growing into the defect area, that is, Ins-PCL / SF / nHA-M has a barrier function.

[0090] In order to demonstrate the effect of SF on the performance of nanofiber films, comparative example 1 is provided, which is a nanofiber film based on polylactic acid-glycolic acid copolymer PLGA, illustrating that PLGA is a conventional drug controlled release carrier and a commonly used electrospinning film raw material.

[0091] Comparison column 1

[0092] A method for preparing a PLGA-based nanofiber film, wherein the steps not specifically described are the same as those in Example 1, except that: in step 1, SF is replaced by PLGA, and the obtained material is referred to as Ins-PCL / PLGA / nHA-M.

[0093] The contact angle test results of Ins-PCL / PLGA / nHA-M are shown in Fig.12 As shown in the figure, the contact angle of Ins-PCL / PLGA / nHA-M is 114.4°, and the hydrophilicity of Ins-PCL / PLGA / nHA-M is poor. The test results show that replacing SF with PLGA can improve the hydrophilicity of the composite material.

[0094] Further hydrophilicity analysis was conducted. According to the previous work of the inventor's research group described in the background, namely the existing document 4, the use of PLGA to prepare PCL / PLGA / nHA nanofiber membranes achieved a contact angle of 128.5°, which also had the technical problem of poor hydrophilicity. However, the purpose of the invention of this technical solution is to prepare a three-dimensional scaffold with a supporting function. Therefore, through the foaming operation, the PCL / PLGA / nHA nanofiber membrane was converted into a PCL / PLGA / nHA three-dimensional scaffold, and the contact angle was significantly reduced to 14.4±2.0°, thereby obtaining good hydrophilicity.

[0095] However, since the technical solution of the present invention does not involve a foaming process, the above-mentioned foaming operation for improving hydrophilicity cannot be used, that is, there is a problem of poor hydrophilicity. Therefore, the present invention needs to adopt an operation based on technical principles to improve hydrophilicity, that is, to adopt the technical feature of replacing PLGA with SF to achieve the technical effect of improving hydrophilicity.

[0096] In order to demonstrate the effect of nHA on the performance of the nanofiber membrane, Comparative Example 2 is provided, which is a nanofiber membrane prepared without adding nHA.

[0097] Comparative Example 2

[0098] A method for preparing a nanofiber film without adding nHA, wherein the steps not specifically described are the same as those in Example 1, except that: in the step 1, nHA is not added, and the obtained material is referred to as Ins-PCL / SF-M.

[0099] The mechanical test results of Ins-PCL / SF-M are as follows Fig.13 The tensile strength of Ins-PCL / SF-M is 2.28MPa, and the tensile strength of Ins-PCL / SF-M is 2.28MPa. The test results show that the addition of nHA can improve the mechanical properties of the composite material by 211%.

[0100] The contact angle test results of Ins-PCL / SF-M are as follows Fig.14 As shown in the figure, the contact angle of Ins-PCL / SF-M is 91.432°, which means that the hydrophilicity is poor. The test results show that adding nHA can improve the hydrophilicity of the composite material.

Claims

1. A nanofiber film with sustained insulin release and barrier function, characterized in that: Polycaprolactone PCL, silk fibroin SF and nano-hydroxyapatite nHA are used as raw materials, hexafluoroisopropanol HFIP is used as solvent, and insulin glargine Ins is used as core layer electrospinning solution. Nanofiber film Ins-PCL / SF / nHA-M with a coaxial shell-core structure is prepared by coaxial electrospinning; the Ins-PCL / SF / nHA-M is hydrophilic and biocompatible.

2. The nanofiber film according to claim 1, characterized in that: The Ins-PCL / SF / nHA-M is in a thin film structure with a thickness of 0.1-0.6 mm; the Ins-PCL / SF / nHA-M is composed of nanofibers with a diameter of 300-600 nm. The nanofibers are randomly arranged with a spacing of 1-20 m between the nanofibers.

3. The nanofiber film according to claim 2, characterized in that: The internal microstructure of the Ins-PCL / SF / nHA-M nanofiber is a coaxial shell-core structure, that is, PCL / SF / nHA wraps glargine insulin, wherein PCL / SF / nHA is a shell layer structure and glargine insulin is a core layer structure.

4. The nanofiber film according to claim 1, characterized in that: The tensile strength of the Ins-PCL / SF / nHA-M is 3.5-6 MPa.

5. A method for preparing a nanofiber film having sustained insulin release and barrier function, characterized in that The following steps are involved: Firstly, polycaprolactone PCL, silk fibroin SF, nano-hydroxyapatite nHA, hexafluoroisopropanol HFIP and insulin glargine Ins satisfy a certain mass ratio, PCL, SF and nHA are placed in HFIP, and magnetic stirring is performed under certain conditions to obtain a shell electrospinning solution. Then, insulin glargine Ins is used as the core electrospinning solution, and coaxial electrospinning is performed with the shell electrospinning solution. After the electrospinning is completed, the obtained product is vacuum dried to obtain a nanofiber film with sustained insulin release and barrier function, which is referred to as Ins-PCL / SF / nHA-M.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the PCL, SF, nHA, HFIP and Ins is 13.3:5.7:1:100:3.

18.

7. The preparation method according to claim 5, characterized in that: The magnetic stirring condition is that the magnetic stirring time is 12-24h; the vacuum drying condition is that the drying temperature is 25-30°C and the drying time is 12-72h; The conditions for the coaxial electrospinning are as follows: before the coaxial electrospinning, the shell electrospinning solution is magnetically stirred for a magnetic stirring time of 12-24 hours, the spinning voltage is 13-15KV, the shell solution injection rate is 0.042-0.06mm / min, the core solution injection rate is 0.015-0.02mm / min, and the collection distance is 10-15cm.

8. A nanofiber film with sustained insulin release and barrier function, characterized in that: When used in the field of bone regeneration, it has sustained-release and barrier functions; The sustained-release function is that there are 4 release stages and the release days are 39 days.

9. The nanofiber film according to claim 1, characterized in that: The sustained-release function has four release stages, namely, Phase 1 was day 1, with insulin release concentrations ranging from 74.40 to 86.52 pg / mL; Phase 2 is from day 2 to day 7, with insulin release concentrations ranging from 98.46 to 240.79 pg / mL; The third stage is from day 14 to day 28, and the insulin release concentration ranges from 60.29 to 88.75 pg / mL; Phase 4 is from day 28 to day 39, and the insulin release concentration range is 35.15-47.01 pg / mL.